Endoscopic drainage combined with percutaneous drainage in treatment of walled-off pancreatic necrosis – a single-center experience - Jagielski, Mateusz; Smoczyński, Marian; Studniarek, Michał; Adrych, Krystian (Gastroenterology Review/Przegląd Gastroenterologiczny, 2018)
Introduction : In last three decades we have been observing development of minimally invasive walled-off pancreatic necrosis (WOPN) treatment techniques. The choice of access to the necrosis and technique of treatment depends not only on the position and spread of necrosis, but in the first place on the experience of the medical center. Aim : To assess the effectiveness and safety of combined endoscopic and percutaneous drainage of WOPN. Material and methods : We performed a retrospective analysis of 64 consecutive patients with symptomatic WOPN, who underwent endoscopic treatment in our department between 2011 and 2013. Results : Additional percutaneous drainage was executed during endoscopic treatment in 20/64 (31.25%) patients. Complications of treatment occurred in 4/20 (20%) patients. Complications of treatment occurred in 4/20 (20%) patients. All these complications were related to endoscopic treatment. No complications related to percutaneous drainage were noted. There were no deaths. Therapeutic success was achieved in all 20 patients. No patients required surgery. The average time of endoscopic drainage was 41.4 (11–173) days. The mean number of endoscopic procedures was 4.2 (2–12). The average time of percutaneous drainage was 11.3 (5–20) days. The medium time of follow-up was 54 (48–64) months. During the observation the recurrence of WOPN was noted in 2/20 (10%) patients. Long-term success of combined drainage was achieved in 18/20 (90%) patients. Conclusions : In selected patients with symptomatic WOPN combined endoscopic and percutaneous drainage enables a high success rate with a low procedure-related complication rate.